Translation of Children’s Picture Book - Agus Darma Yoga Pratama (RETORIKA: Jurnal Ilmu Bahasa, 2019)
Children’s story books serve not only as a medium of verbal communication but also as that of non-verbal one. Messages conveyed through children’s story books will not be attracting to children if not accompanied by their non-verbal forms, such as pictures and symbols. Therefore every story book should be able to influence the child psychologically through pictures or symbols. This in turn affects the process of translating children’s storybook texts, including in determining translation techniques. This study examines the technique of translating Balinese children’s story books from English into Indonesian. This study was conducted with a qualitative research design. The results of the study show that the translation of Balinese children’s textbooks is mostly done literally using simple language. The writing children’s story books emphasizes the presentation of non-verbal forms of communication to foster and maintain their interest in reading. The writing and translation of children’s story texts is based on consideration of their psychological aspects so that the translator avoids the use of complicated words.